The Globalization of World Politics: An Introduction to International Relations - Baylis, John; Smith, Steve and Owens, Patricia (New York Oxford University Press, 2020)
The best-selling introduction to international relations offers the most comprehensive coverage of the key theories and global issues in world politics, written by the leading experts in the field
Include Map, Color Illustration,Reference and Index
Keywords: International relations -- World Politics -- Globalization